LANGUAGE AND CULTURE: THE CURRICULUM GUIDELINES FOR TEACHING FOREIGN LANGUAGE - Almeida, Jessica Chagas de [UNESP]; Rocha, Nildiceia Aparecida [UNESP] (Unesp-faculdade Ciencias & Letras, 2019)
The Brazilian document Orientacoes Curriculares do Ensino Medio (OCEM) values the plurality and heterogeneity of the language, the contact with the other and the reflection on cultural diversities. Therefore, the aim of this article is to verify which culture concept(s) emerges through the reading of the document and to relate how it has been understood in the teaching and learning of a foreign language. For this work, we mobilized, as a methodological and analytical framework, the concept of interdiscourse, within the scope of French Discoursive Analysis. We noticed that OCEM suggests an intrinsic work between language and culture. Such notions complete each other, due to the fact that the language is in the culture and vice-versa. Although it does not mention, the analytical retake to the interdiscourse allows the observation that the discursiveness of the document deals with several authors. This work shows such important concepts for teaching and learning languages, as well as highlighting their importance.
Keywords: Language and culture; OCEM; Linguistic policy; Speech; Teaching and learning